2016
DOI: 10.1007/s11433-015-5768-2
|View full text |Cite
|
Sign up to set email alerts
|

Rapidity distribution of protons from the potential version of UrQMD model and the traditional coalescence afterburner

Abstract: Rapidity distributions of both E895 proton data at AGS energies and NA49 net proton data at SPS energies can be described reasonably well with a potential version of the UrQMD in which mean-field potentials for both pre-formed hadrons and confined baryons are considered, with the help of a traditional coalescence afterburner in which one parameter set for both relative distance R 0 and relative momentum P 0 , (3.8 fm, 0.3 GeV/c), is used. Because of the large cancellation between the expansion in R 0 and the s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…As a matter of experience, the values for the parameter set (R 0 , P 0 ) might be chosen in the range of (3-4 fm, 0.25-0.35 GeV/c) in order to describe experimental data from HICs at SIS, AGS, and even SPS energies. Within such a large beam energy region, the relativistic effect on δr and δp between two baryons have been taken into account by the well-known Lorentz transformation (LT) from the computational two-nucleus center-of-mass system to the local rest frame of two particles [16,17], and it is found that it has visible effect on light fragments, although not on free nucleons, which should be paid attention.…”
Section: The Urqmd and The Coalescence Model Settingsmentioning
confidence: 99%
See 1 more Smart Citation
“…As a matter of experience, the values for the parameter set (R 0 , P 0 ) might be chosen in the range of (3-4 fm, 0.25-0.35 GeV/c) in order to describe experimental data from HICs at SIS, AGS, and even SPS energies. Within such a large beam energy region, the relativistic effect on δr and δp between two baryons have been taken into account by the well-known Lorentz transformation (LT) from the computational two-nucleus center-of-mass system to the local rest frame of two particles [16,17], and it is found that it has visible effect on light fragments, although not on free nucleons, which should be paid attention.…”
Section: The Urqmd and The Coalescence Model Settingsmentioning
confidence: 99%
“…produced in nucleon-induced spallation reactions. Quite recently, the traditional coalescence afterburner has been combined with a potential version of UrQMD model to explain the production of free protons and 3 He clusters from HICs at the Brookhaven Alternating Gradient Synchroton (AGS) and the CERN Super Proton Synchrotron (SPS) energies [16,17] and it was found that, with only one parameter set of (R 0 ,P 0 )=(3.8 fm, 0.3 GeV/c) but using different stopping times for the former dynamic process, the rapidity distribution of both yields can be described reasonably well.…”
mentioning
confidence: 99%
“…[39]. The experimental data of heavy-ion collisions in intermediate energies can be reproduced reasonably well by this model [39][40][41][42][43][44][45].…”
Section: Magnetic Field Calculations In Urqmdmentioning
confidence: 53%
“…By this method, if the relative distances and momenta of two nucleons are smaller than and , respectively, they are considered to belong to the same fragment. With a proper set of and , the fragment mass distribution in HICs at intermediate energies is efficiently reproduced [45][46][47]. The parameters adopted in this study are The collective flow in HICs was studied extensively to deduce properties of formed hot and dense matter.…”
Section: Resultsmentioning
confidence: 99%